Zulna Fiqih Siyasah On Bnn's Duties in Overcoming Drug Trafficking According to Bnn Regulation Number 5 Of 2020 (Case Study of Tanjung Selamat District, Padang Tualang District, Langkat Regency) - M. Nashuha; Zulkarnain (Journal Equity of Law and Governance, 2024)
Countering drug trafficking is one of the major challenges in maintaining public safety and welfare. This study focuses on BNN Regulation Number 5 of 2020 and its implementation in Tanjung Selamat Village, Padang Tualang District, Lalat Regency, and looks at the perspective of fiqh siyasah on the duties of the National Narcotics Agency (BNN) in dealing with drug trafficking. The type of research in this case is empirical juridical with a sociological approach. Primary data was obtained through an interview process with related parties. The results of the study show that despite obstacles such as budget limitations and limited access, BNN's efforts in Tanjung Selamat Village are in line with the principles of justice and protection in fiqh siyasah. The results show that, in the context of fiqh siyasah, BNN regulation Number 5 of 2020 concerning the organization and governance of the National Narcotics Agency supports the government's efforts to protect the public from the dangers of drugs and provides guidance to increase the effectiveness of local drug control strategies.